2022
DOI: 10.1002/agg2.20271
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater‐recycled struvite as a phosphorus source in a wheat–soybean double‐crop production system in eastern Arkansas

Abstract: Fertilizer-phosphorus (P) sources are mainly derived from rock phosphate (RP), which is a finite, actively mined resource. With growing human populations globally, alternative P sources are vitally important to ensure future food security. Precipitation of the mineral struvite (MgNH 4 PO 4 •6H 2 O) from wastewater could be a potential alternative fertilizer-P option from crop production. The objective of this study was to evaluate the effects of chemically precipitated struvite (CPST), compared with triple sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
8
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 61 publications
9
8
5
Order By: Relevance
“…However, averaged across fertilizer‐P treatments, aboveground tissue Mg concentration was 1.2‐times greater ( P = .01) in 2020 than in 2019 (Table 6). In contrast to the results of the current study, Omidire and Brye (2022) documented that aboveground soybean tissue Mg concentration was 1.1‐times greater from CPST than from TSP or the UC, which did not differ.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…However, averaged across fertilizer‐P treatments, aboveground tissue Mg concentration was 1.2‐times greater ( P = .01) in 2020 than in 2019 (Table 6). In contrast to the results of the current study, Omidire and Brye (2022) documented that aboveground soybean tissue Mg concentration was 1.1‐times greater from CPST than from TSP or the UC, which did not differ.…”
Section: Resultscontrasting
confidence: 99%
“…Aboveground tissue P uptake from CPST, which was comparable to DAP or TSP, was at least 1.1‐times greater than that from MAP and at least 1.2‐times greater than that from RP or the UC (Table 5). In contrast to the current study, Omidire and Brye (2022) reported no difference in soybean aboveground tissue P uptake among CPST, TSP, and the UC treatment.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations